Hydroanthropological Aspects of the Winongo River Geguritan - Sintha Wijayanti; Afendy Widayat (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Bardikari Jarmiko's Geguritan Kali Winongo has an idea of the water cycle that has a big hand in the life of mankind. So that humans cannot be separated from water and all its various forms, including rivers and streams. The author is interested in studying the literature in hydrological and anthropological aspects. So, it is hoped that this research will be able to produce another perspective on Geguritan literature related to water and human behavior. This research is qualitative descriptive research, using a multidisciplinary approach that seeks to combine several disciplines to solve or overcome certain problems. The object of this study is a Geguritan entitled Kali Winongo by Bardikari Jarmiko. There is a hydrological cycle contained in the Geguritan related springs that appear upstream (mountains). As is the nature of the water flowing to the lower places passing through various forms of the soil surface.  Also in the water cycle there is a network of rivers consisting of the union of rivers - small rivers into larger rivers. The Winongo River contains advice and reminders about the importance of rivers and water in human life. The existence of living and life-giving water provides benefits to people's daily activities. Humans can befriend nature, but they can also be threatened by nature's response to human behavior.